The Burden of Peripheral Artery Disease in China From 1990 to 2019 and Forecasts for 2030: Findings From the Global Burden of Disease Study 2019 - Ye Hu; Ye Hu; Jiyue Gao; Jiyue Gao; Qiping Zhuo; Qiping Zhuo; Huixin Liu; Meiling Wang; Meiling Wang; Nina Jiang; Nina Jiang; Xueqing Wang; et al. (International Journal of Public Health)
ObjectivesThe incidence of peripheral arterial disease (PAD) in China is increasing. We aim to conduct a comprehensive analysis of the burden of PAD.MethodsWe collected information from 1990 to 2019 in the Global Burden of Disease (GBD 2019) study. Joinpoint regression analysis was used to calculate the annual percentage change (APC). Trends in incidence, mortality and DALYs were forecasted by Bayesian age-period-cohort (BAPC) analysis.ResultsIn 2019, the number of new cases and prevalence of PAD in China accounted for nearly a quarter of the global proportion. The age-standardized incidence rate (ASIR) declined after rising until 2005. The age-standardized death rate (ASDR) maintained an upward trend. The DALYs was 0.16 million. Incidence, prevalence and DALYs are predominantly female, except for mortality, which is predominantly male. Smoking predominantly affected males, while hypertension and diabetes had a greater impact on females. By 2030, ASDR is elevated, predominantly in males. ASIR and age-standardized DALY rate decline, predominantly in females.ConclusionIt is urgent for China to develop strategies based on the specific distribution characteristics of the PAD burden.